A nonisothermal study of the kinetics of the nanoporosity elimination in sonogels-derived silica xerogels - Vollet, D. R.; de Castro, W. C.; Donatti, D. A.; Ruiz, A. I. (Amer Chemical Soc, 2005)
A nonisothermal study of the kinetics of the nanoporosity elimination in monolithic silica xerogels, prepared from acid and ultrasound catalyzed hydrolysis of tetraethylortosilicate (TEOS), has been carried out by means of in situ linear shrinkage measurements performed with different heating rates. The study could be applied up to almost alpha similar to 0.6 of the volume fraction alpha of eliminated pores. The activation energy was found increasing from about 3.2 x 10(2) kJ/mol for alpha similar to 0.06 up to about 4.4 x 10(2) kJ/mol for alpha. similar to 0.44. The sintering process accompanying the nanopore elimination in this set of xerogels is in agreement with a viscous flux sintering process with the hydroxyl content diminishing with the volume fraction of eliminated pores. All the volume fraction of eliminated pores versus temperature (T) curves can be matched onto a unique curve with an appropriate rescaling of the T axis, independent of the heating rate. This scaling property suggests that the path of sintering seems the same, regardless of the heating rate; the difference is that the rate is faster at higher temperature.